Prospects of International Legal Cooperation of States Under U.N. Auspices in Developing a Treaty on Transnational Corporations and Other Business Enterprises with Respect to Human Rights - D. Ivanov; M. Levina (BRICS Law Journal, 2021)
The present article is a review of the prospective adoption of a legally binding instrument to regulate, in international human rights law, the activities of transnational corporations (TNCs) and other business enterprises presently being developed under U.N. auspices, aiming for legal control of TNCs’ business functioning. The necessity for international legal control of their business’ functioning with respect to human rights cannot be underestimated as their influence has grown since striving for dominance in world commodity markets and in leading sectors of the global economy. However, quite a number of scholars question the fact that TNCs are not presently recognized as legal personalities rendering the immediate application of international law principles to their business activities all but practically impossible. At the same time, the majority of so called “soft law” principles developed in the U.N. framework in the past fifty years are nothing more than recommendations to TNCs, thus, emphasizing the urgency of developing a legally binding instrument which primarily governs transnational corporations with respect to human rights. Nevertheless, the prospective adoption of a future treaty, currently being developed by the Open-ended Intergovernmental Working Group on Transnational Corporations and other Business Enterprises with Respect to Human Rights, does not look highly promising due to a number of fundamental flaws and inconsistencies analyzed below.